Early start of hemoadsorption is associated with improved kidney recovery in ICU patients with ischemic/reperfusion cause of rhabdomyolysis - Vedran Premuzic; Alan Horvat; Mate Mogus; Ivona Vucic; Ivan Situm; Tina Tomic-Mahecic; Zeljko Colak; Mirabel Mazar; Robert Baronica; Slobodan Mihaljevic (PLoS ONE, 2026)
Background Hemoadsorption is considered currently as an adjunct therapy for the treatment of rhabdomyolysis and acute kidney injury (AKI) although the exact timing is not yet determined. We hypothesised that earlier start of hemoadsorption in patients with ischemia/reperfusion caused rhabdomyolysis and AKI leads to a better clinical improvement and recovery of kidney function. Materials and methods We conducted a single-center, retrospective cohort study. Treatment was defined as the use of hemoadsorption with CytoSorb® in combination with continuous renal replacement therapy (CRRT) compared to patients who were treated only with CRRT. Patients were divided in early and late initiation of hemoadsorption subgroups by less or more than 12 hours after developing acute kidney injury. Myoglobin and creatine kinase plasma levels were measured shortly before, 12 hours after the start of treatment, and 24, 48, and 72 hours after initiation. The follow-up lasted until the last enrolled patient reached 60 days after first hemoadsorption procedure. Results Overall, 30 patients were included in the treatment arm and 25 patients in the control group. Significant decrease of myoglobin levels was observed in the hemoadsorption treated group in all time points when compared with the control group. Logistical regression analysis found the association of hemoadsorption use and shorter duration of AKI (OR 3.46) and less acute kidney disease (AKD) (OR 2.85). Earlier start of hemoadsorption was associated with a statistically significant shorter duration of AKI (OR 3.22) and less AKD (OR 3.10). Patients treated early with hemoadsorption survived significantly longer than patients treated late (49.2 vs 15.3 days; p < 0.001). Conclusions Early start of combined CRRT and hemoadsorption therapy with CytoSorb was safe and associated with improved kidney recovery and survival in patients with ischemic/reperfusion rhabdomyolysis and AKI. Early start of hemoadsorption might prevent renal failure and acute kidney disease and shorten the CRRT dependency in patients who develop AKI.